Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

On the origin of the late-flowering ppd-H1 allele in barley - Rajiv Sharma; Salar Shaaf; Kerstin Neumann; Peter Civan; Yu Guo; Martin Mascher; Michal David; Adnan Al-Yassin; Hakan Özkan; Tom Blake; Sariel Hübner; Nora P. Castañeda-Álvarez; et al. (Theoretical and Applied Genetics, 2025)
To breed for climate resilient crops, an understanding of the genetic and environmental factors influencing adaptation is critical. Barley provides a model species to study adaptation to climate change. Here we present a detailed analysis of genetic variation at a major photoperiod response locus and relate this to the domestication history and dispersal of barley. The PPD-H1 locus (a PSEUDO-RESPONSE REGULATOR 7 ) promotes flowering under long-day conditions, and a natural mutation at this locus resulted in a recessive, late-flowering ppd-H1 allele. This mutation proved beneficial in high-latitude environments such as Northern Europe, where it allows extended vegetative growth during long spring days. We infer the origin of the mutated late-flowering ppd-H1 allele by re-sequencing a large geo-referenced collection of 942 Hordeum spontaneum , 5 Hordeum agriocrithon and 1110 domesticated ( Hordeum vulgare ) barleys. We demonstrate that the late-flowering phenotype originated from Desert-type wild barley in the Southern Levant and present evidence suggesting a post-domestication origin of the mutated ppd-H1 allele.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Perfluorodecanoic acid (PFDA) increases oxidative stress through inhibition of mitochondrial β-oxidation - Raimund Widhalm; Sebastian Granitzer; Benjamin Natha; Ottavia Zoboli; Julia Derx; Harald Zeisler; Hans Salzer; Stefan Weiss; Nicole Schmitner; Robin A. Kimmel; Tamina Österreicher; Raimund Oberle; et al. (Environmental Pollution, 2025)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Statistical reanalysis of Archean zircon paleointensities: No evidence for stagnant-lid tectonics - Roger R. Fu; Nadja Drabon; Benjamin P. Weiss; Cauê Borlina; Heather Kirkpatrick (Earth and Planetary Science Letters, 2024)

Sediment analysis and historical context of the 2018 Palu-Donggala tsunami deposit, Indonesia - Jędrzej M. Majewski; Adam D. Switzer; Rachel Y.S. Guan; Benazir Benazir; Ella Meilianda; Peter R. Parham; Robert Weiss; Stacey S. Martin; Lillian K. Pearson; Jessica E. Pilarczyk; Patrick Daly; Benjamin P. Horton (Marine Geology, 2023)

Pb diffusion in magnetite: Dating magnetite crystallization and the timing of remanent magnetization in banded iron formation - E. Bruce Watson; Daniele J. Cherniak; Claire I.O. Nichols; Benjamin P. Weiss (Chemical Geology, 2023)

Restoration ecology through the lens of coexistence theory - Lauren M. Hallett; Lina Aoyama; György Barabás; Benjamin Gilbert; Loralee Larios; Nancy Shackelford; Chhaya M. Werner; Oscar Godoy; Emma R. Ladouceur; Jacob E. Lucero; Christopher P. Weiss-Lehman; Jonathan M. Chase; et al. (Trends in Ecology & Evolution, 2023)

Paleogeography and high-precision geochronology of the Neoarchean Fortescue Group, Pilbara, Western Australia - Jennifer Kasbohm; Blair Schoene; Scott A. Maclennan; David A.D. Evans; Benjamin P. Weiss (Precambrian Research, 2023)

Fungal symbiont community and absence of detectable mycangia in invasive Euplatypus ambrosia beetles - Andre Rodrigues; Andrew J. Johnson; Ross A. Joseph; You Li; Nemat O. Keyhani; Edward L. Stanley; Benjamin Weiss; Martin Kaltenpoth; Matthew E. Smith; Jiri Hulcr (Symbiosis, 2023)

Effects of aluminum ion on particle sizes and surface charges of exopolysaccharides from Rhizobium tropici and pH effects - Steve L. Larson; John H. Ballard; Kauri A. Runge; Huimin Zhang; Benjamin R. Breland; Zachary H. Nick; Ethan Tyler Vroman; Charles A. Weiss; Fengxiang X. Han (Rhizosphere, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Displacement Effects of Conservation Grazing on Red Deer (Cervus elaphus) Spatial Behaviour - Fabio Weiss; Frank Uwe Michler; Benjamin Gillich; Jörg Tillmann; Simone Ciuti; Marco Heurich; Siegfried Rieger (Environmental Management, 2022)
Conservation grazing uses semi-feral or domesticated herbivores to limit encroachment in open areas and to promote biodiversity. However, we are still unaware of its effects on wild herbivores. This study investigates the influence of herded sheep and goats on red deer ( Cervus elaphus ) spatial behavior by testing three a-priori hypotheses: (i) red deer are expected to avoid areas used by livestock, as well as adjacent areas, when livestock are present, albeit (ii) red deer increase the use of these areas when sheep and goats are temporarily absent and (iii) there is a time-lagged disruption in red deer spatial behavior when conservation grazing practice ends. Using GPS-telemetry data on red deer from a German heathland area, we modelled their use of areas grazed by sheep and goats, using mixed-effect logistic regression. Additionally, we developed seasonal resource selection functions (use-availability design) to depict habitat selection by red deer before, during, and after conservation grazing. Red deer used areas less during conservation grazing throughout all times of the day and there was no compensatory use during nighttime. This effect mostly persisted within 21 days after conservation grazing. Effects on habitat selection of red deer were detectable up to 3000 meters away from the conservation grazing sites, with no signs of either habituation or adaption. For the first time, we demonstrate that conservation grazing can affect the spatio-temporal behavior of wild herbivores. Our findings are relevant for optimizing landscape and wildlife management when conservation grazing is used in areas where wild herbivores are present.

Ilmenite and magnetite microfabrics in shocked gneisses from the Vredefort impact structure, South Africa - Fabian Dellefant; Claudia A. Trepmann; Stuart A. Gilder; Iuliia V. Sleptsova; Melanie Kaliwoda; Benjamin P. Weiss (Contributions to Mineralogy and Petrology, 2022)
We investigated microfabrics of shocked Archean gneisses from two, 10 m-deep drill cores located near the center of the Vredefort impact structure in an area that is characterized by a prominent, long-wavelength negative magnetic anomaly (< − 3000 nT) together with short-wavelength, high-amplitude anomalies attributed to lightning strikes. Planar fractures and feather features in quartz, which can be partially recrystallized, indicate shock conditions less than 20 GPa. Micrometer-sized magnetite and ilmenite along shock-related shear fractures in quartz and feldspar emanate from adjacent deformed coarse (> 100 µm) ilmenite and magnetite host grains. These fine-scaled veins suggest mobilization of magnetite and ilmenite during shear deformation of host Fe-phases and adjacent silicates, probably associated with frictional heating. Coarse ilmenite has fine-lamellar mechanical twins parallel to {10 $$\overline{1}$$ 1 ¯ 1} and single (0001) twins, indicative of dislocation-glide-controlled deformation under non-isostatic stresses related to shock. A few µm-wide magnetite lamellae parallel to {10 $$\overline{1}$$ 1 ¯ 1} and spheroidal magnetite (diameter ≈10 µm) within coarse ilmenite document exsolution after shock. Dauphiné twins associated with planar features in quartz imply cooling from 650 to 725 °C after shock, which accords with estimates of pre-impact basement temperatures from petrographic studies. The Curie temperature of magnetite is 580 °C; therefore, the central negative magnetic anomaly was produced as a thermoremanent magnetization acquired during cooling of the initially hot crust. The long-wavelength anomaly was likely amplified by the newly created magnetite that also acquired a thermal remanence. Although the magnetic properties of surface samples are often influenced by lightning strikes, we found no microstructural evidence for lightning-related processes.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

ENDURUNS: An Integrated and Flexible Approach for Seabed Survey Through Autonomous Mobile Vehicles - Simone Marini; Nikolla Gjeci; Shashank Govindaraj; Alexandru But; Benjamin Sportich; Ennio Ottaviani; Fausto Pedro García Márquez; Pedro Jose Bernalte Sanchez; Jonas Pedersen; Casper Vetke Clausen; Fantina Madricardo; Fedeirca Foglini; et al. (Journal of Marine Science and Engineering, 2020)
The oceans cover more than two-thirds of the planet, representing the vastest part of natural resources. Nevertheless, only a fraction of the ocean depths has been explored. Within this context, this article presents the H2020 ENDURUNS project that describes a novel scientific and technological approach for prolonged underwater autonomous operations of seabed survey activities, either in the deep ocean or in coastal areas. The proposed approach combines a hybrid Autonomous Underwater Vehicle capable of moving using either thrusters or as a sea glider, combined with an Unmanned Surface Vehicle equipped with satellite communication facilities for interaction with a land station. Both vehicles are equipped with energy packs that combine hydrogen fuel cells and Li-ion batteries to provide extended duration of the survey operations. The Unmanned Surface Vehicle employs photovoltaic panels to increase the autonomy of the vehicle. Since these missions generate a large amount of data, both vehicles are equipped with onboard Central Processing units capable of executing data analysis and compression algorithms for the semantic classification and transmission of the acquired data.

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

The protein corona suppresses the cytotoxic and pro-inflammatory response in lung epithelial cells and macrophages upon exposure to nanosilica - Regina Leibe; I-Lun Hsiao; Susanne Fritsch-Decker; Ulrike Kielmeier; Ane Marit Wagbo; Benjamin Voss; Annemarie Schmidt; Sarah Dorothea Hessman; Albert Duschl; Gertie Janneke Oostingh; Silvia Diabaté; Carsten Weiss (Archives of Toxicology, 2019)

Atmospheric histories, growth rates and solubilities in seawater and other natural waters of the potential transient tracers HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116 - Pingyang Li; Jens Mühle; Stephen A. Montzka; David E. Oram; Benjamin R. Miller; Ray F. Weiss; Paul J. Fraser; Toste Tanhua (Ocean Science, 2019)
We present consistent annual mean atmospheric histories and growth rates for the mainly anthropogenic halogenated compounds HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116, which are all potentially useful oceanic transient tracers (tracers of water transport within the ocean), for the Northern and Southern Hemisphere with the aim of providing input histories of these compounds for the equilibrium between the atmosphere and surface ocean. We use observations of these halogenated compounds made by the Advanced Global Atmospheric Gases Experiment (AGAGE), the Scripps Institution of Oceanography (SIO), the Commonwealth Scientific and Industrial Research Organization (CSIRO), the National Oceanic and Atmospheric Administration (NOAA) and the University of East Anglia (UEA). Prior to the direct observational record, we use archived air measurements, firn air measurements and published model calculations to estimate the atmospheric mole fraction histories. The results show that the atmospheric mole fractions for each species, except HCFC-141b and HCFC-142b, have been increasing since they were initially produced. Recently, the atmospheric growth rates have been decreasing for the HCFCs (HCFC-22, HCFC-141b and HCFC-142b), increasing for the HFCs (HFC-134a, HFC-125, HFC-23) and stable with little fluctuation for the PFCs (PFC-14 and PFC-116) investigated here. The atmospheric histories (source functions) and natural background mole fractions show that HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125 and HFC-23 have the potential to be oceanic transient tracers for the next few decades only because of the recently imposed bans on production and consumption. When the atmospheric histories of the compounds are not monotonically changing, the equilibrium atmospheric mole fraction (and ultimately the age associated with that mole fraction) calculated from their concentration in the ocean is not unique, reducing their potential as transient tracers. Moreover, HFCs have potential to be oceanic transient tracers for a longer period in the future than HCFCs as the growth rates of HFCs are increasing and those of HCFCs are decreasing in the background atmosphere. PFC-14 and PFC-116, however, have the potential to be tracers for longer periods into the future due to their extremely long lifetimes, steady atmospheric growth rates and no explicit ban on their emissions. In this work, we also derive solubility functions for HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116 in water and seawater to facilitate their use as oceanic transient tracers. These functions are based on the Clark–Glew–Weiss (CGW) water solubility function fit and salting-out coefficients estimated by the poly-parameter linear free-energy relationships (pp-LFERs). Here we also provide three methods of seawater solubility estimation for more compounds. Even though our intention is for application in oceanic research, the work described in this paper is potentially useful for tracer studies in a wide range of natural waters, including freshwater and saline lakes, and, for the more stable compounds, groundwaters.

Major challenges of integrating agriculture into climate change mitigation policy frameworks - Thomas Fellmann; Peter Witzke; Franz Weiss; Benjamin Van Doorslaer; Dusan Drabik; Ingo Huck; Guna Salputra; Torbjörn Jansson; Adrian Leip (Mitigation and Adaptation Strategies for Global Change, 2018)

Li zoning in zircon as a potential geospeedometer and peak temperature indicator - Dustin Trail; Daniele J. Cherniak; E. Bruce Watson; T. Mark Harrison; Benjamin P. Weiss; Ian Szumila (Contributions to Mineralogy and Petrology, 2016)

High end GPCR design: crafted ligand design and druggability analysis using protein structure, lipophilic hotspots and explicit water networks - Jonathan S Mason; Andrea Bortolato; Dahlia R Weiss; Francesca Deflorian; Benjamin Tehan; Fiona H Marshall (In Silico Pharmacology, 2013)
Purpose G Protein-Coupled Receptors (GPCRs) are a large family of therapeutically important proteins and as diverse X-ray structures become available it is increasingly possible to leverage structural information for rational drug design. We present herein approaches that use explicit water networks combined with energetic surveys of the binding site (GRID), providing an enhanced druggability and ligand design approach, with structural understanding of ligand binding, including a ‘magic’ methyl and binding site mutations, and a fast new approach to generate and score waters. Methods The GRID program was used to identify lipophilic and hydrogen bonding hotspots. Explicit full water networks were generated and scored for (pseudo)apo structures and ligand-protein complexes using a new approach, WaterFLAP (Molecular Discovery), together with WaterMap (Schrödinger) for (pseudo)apo structures. A scoring function (MetaScore) was developed using a fast computational protocol based on several short adiabatic biased MD simulations followed by multiple short well-tempered metadynamics runs. Results Analysis of diverse ligands binding to the adenosine A 2A receptor together with new structures for the δ/κ/μ opioid and CCR5 receptors confirmed the key role of lipophilic hotspots in driving ligand binding and thus design; the displacement of ‘unhappy’ waters generally found in these regions provides a key binding energy component. Complete explicit water networks could be robustly generated for protein-ligand complexes using a WaterFLAP based approach. They provide a structural understanding of structure-activity relationships such as a ‘magic methyl’ effect and with the metadynamics approach a useful estimation of the binding energy changes resulting from active site mutations. Conclusions The promise of full structure-based drug design (SBDD) for GPCRs is now possible using a combination of advanced experimental and computational data. The conformational thermostabilisation of StaR® proteins provide the ability to easily generate biophysical screening data (binding including fragments, kinetics) and to get crystal structures with both potent and weak ligands. Explicit water networks for apo and ligand-complex structures are a critical ‘third dimension’ for SBDD and are key for understanding ligand binding energies and kinetics. GRID lipophilic hotspots are found to be key drivers for binding. In this context ‘high end’ GPCR ligand design is now enabled.

Dominance of the odometer over serial landmark learning in honeybee navigation - Randolf Menzel; Jacqueline Fuchs; Leonard Nadler; Benjamin Weiss; Nicole Kumbischinski; Daniel Adebiyi; Sergej Hartfil; Uwe Greggers (The Science of Nature, 2010)

Medical history, body size, and cigarette smoking in relation to fatal prostate cancer - Sheila Weinmann; Jean A. Shapiro; Benjamin A. Rybicki; Shelley M. Enger; Stephen K. Van Den Eeden; Kathryn E. Richert-Boe; Noel S. Weiss (Cancer Causes & Control, 2010)

The Glenohumeral Capsule Should be Evaluated as a Sheet of Fibrous Tissue: A Validated Finite Element Model - Susan M. Moore; Benjamin Ellis; Jeffrey A. Weiss; Patrick J. McMahon; Richard E. Debski (Annals of Biomedical Engineering, 2010)

Noninvasive Determination of Ligament Strain with Deformable Image Registration - Nikhil S. Phatak; Qunli Sun; Seong-Eun Kim; Dennis L. Parker; R. Kent Sanders; Alexander I. Veress; Benjamin J. Ellis; Jeffrey A. Weiss (Annals of Biomedical Engineering, 2007)

Acute meningoencephalitis caused by adenovirus serotype 26 - Erik R Dubberke; Benjamin Tu; Dennis J Rivet; Gregory A Storch; Anucha Apisarnthanarak; Robert E Schmidt; Stuart Weiss; Louis B Polish (Journal of NeuroVirology, 2006)